Identifikasi dan Penilaian Risiko Stakeholder pada Proyek Infrastruktur Pertambangan Nikel: Studi Kasus di Pertambangan Nikel PT. X - Kerri Dwiky Iswara; Wisnu Isvara; Titi Sari Nurul Rachmawati (Fakultas Teknik Universitas Cenderawasih, 2026)
The growth of the nickel mining industry in Indonesia, particularly in Southeast Sulawesi Province, has made this sector one of the main contributors to the Regional Gross Domestic Product (RGDP). However, the development of supporting infrastructure—especially mining haulage roads—still faces various risks that could potentially cause project delays and disrupt operational efficiency. Therefore, a systematic risk identification process is necessary to ensure that project implementation proceeds in accordance with established time, cost, and quality targets. This study aims to identify and assess risks in mining infrastructure development projects using a stakeholder-based approach. This approach is employed to gain an understanding of the risks that arise from the perspectives of the parties involved in the project. The results of this study describe the dominant risks that could potentially occur in nickel mining projects, namely opposition from the local community surrounding the project, conflicts with community organizations, denial of access to project roads, and disruption of project security due to inadequate security measures by authorities. It is hoped that these dominant risks can serve as a basis for developing effective risk mitigation strategies to support the successful and sustainable development of mining infrastructure.